Dietary salt and the glycaemic response to meals of different fibre content (1989)
In attempting to resolve the existing controversy on the effect of dietary salt intake on glycaemic responses, wc investigated post-prandial plasma glucose levels in 10 healthy normal weight non-diabetic Nigerian subjects (aged 23.1 years ± 1.3 (s.e.m.) with body mass index, BMI 19.9 ± 0.6kg/m2) consuming equal amounts of carbohydrate from glucose, boiled yam (tow fibre content of 0.9 per cent raw tuber weight) and boiled black-eyed peas (high fibre content of 4.8 per cent dry weight) with and without added table salt (4.25g). The results indicated no significant differences in fasting, peak and 2-h plasma glucose concentrations and total and incremental areas under the 3-h glucose/time curves in the subjects consuming each meal with and without added salt. Added salt had no influence on the glycaemic index of each meal. We conclude that salt has no effect on the glycaemic response to plain glucose or meals with varying fibre content even in a population known to demonstrate defects in salt handling.